Facile regioselective decomposition of tosylhydrazones: an application towards the synthesis of alpha-lipoic acid - Chavan, Subhash P.; Kale, R. R.; Pasupathy, K. (Synlett, 2005)
A facile regioselective decomposition of tosylhydrazones using NaOH as a base in refluxing isopropyl alcohol is described. This finding has been Successfully applied towards the synthesis of (&PLUSMN;)-α-lipoic acid (1).
Keywords: alpha-lipoic acid; Olefins; Regioselectivity; tosylhydrazones